Model Pembangunan Demokrasi di Tingkat Akar Rumput (Studi Peran JRMK Dalam Pembangunan Kampung Kota di Jakarta Tahun 2017-2022) - Mahroza, Dekki (Universitas Nasional, 2023)
After the fall of the Orde Baru regime, Indonesia entered a transitional phase of democracy, one of which was marked by the holding national and regional elections. However, the ongoing development of democracy experienced setbacks. One form of setbacks is electoral democracy that dominated by oligarchs. The oligarchs are supported by a capitalistic economic system and a corrupt political culture such as the practice of money politics which spreads during the implementation of electoral democracy. Because of this, a model for development democracy must be built that can prevent the public from being tempted by money politics and open up wide participation of the public in elections. Urban village development by JRMK also reflected democracy development, starting from the involvement of citizens and JRMK in the 2017 DKI Jakarta governor election through a political contract with one of the governor candidates, namely Anies Baswedan, to the process of formulating village development policies involving the role of the peblic. This research examines the role of a community organization, namely the City Poor People's Network (JRMK) in the development of urban villages in Jakarta in 2017-2022 by looking at it from the perspective of democracy development. This aspect of democracy can be seen starting from JRMK's role in encouraging residents to be actively involved in the moment of the 2017 DKI Jakarta gubernatorial election to encouraging citizen participation in the village development process, be it physical village development such as settlements, village roads, sanitation, as well as human development both from a political perspective, economic, and socio-cultural.Setelah kejatuhan rezim Orde Baru, Indonesia memasuki tahap transisi demokrasi yang salah satunya ditandai dengan pelaksanaan pemilu nasional dan daerah. Namun pembangunan demokrasi yang berjalan mengalami kemunduran. Bentuk kemundurannya antara lain adalah demokrasi elektoral yang dikuasai kelompok oligarki. Kaum oligarki didukung oleh sistem ekonomi kapitalistik dan budaya politik korup seperti praktek politik uang yang merebak pada saat pelaksanaan demokrasi elektoral. Karena itu harus dibangun model pembangunan demokrasi yang dapat menghindari masyarakat dari godaan politik uang dan membuka luas partisipasi masyarakat dalam pemilu. Pembangunan kampung oleh JRMK juga mencerminkan pembangunan demokrasi, yang dimulai dari keterlibatan warga dan JRMK dalam pemilihan gubernur DKI Jakarta tahun 2017 melalui kontrak politik dengan salah satu calon gubernur yakni Anies Baswedan hingga proses perumusan kebijakan pembangunan kampung yang melibatkan peran warga. Penelitian ini mengkaji mengenai peran suatu organisasi komunitas yakni Jaringan Rakyat Miskin Kota (JRMK) dalam pembangunan kampung kota di Jakarta tahun 2017-2022 dengan melihatnya dalam perspektif pembangunan demokrasi. Aspek demokrasi ini bisa dilihat dimulai dari peran JRMK dalam mendorong warga terlibat aktif dalam momen pemilihan gubernur DKI Jakarta 2017 hingga mendorong partisipasi warga dalam proses pembangunan kampung, baik itu pembangunan fisik kampung seperti pemukiman, jalan kampung, sanitasi, maupun pembangunan manusianya baik dari sisi politik, ekonomi, dan sosial-budaya.